ABO-INCOMPATIBLE PEDIATRIC LIVER TRANSPLANTATION: THE ANALYSIS OF WORLD EXPERIENCE - I. E. Tsirulnikova; O. P. Shevchenko (Вестник трансплантологии и искусственных органов, 2012)
In the review we present the world scientific literature data analysis of the results of ABO-incompatible liver transplantation in children and adults. Used previously and modern protocols of pre- and postoperative manage- ment of ABO-incompatible recipients from different transplant centers are described. While adult ABO-incom- patible liver transplantation is still linked with increased risk of immune complications, short and long-term results of ABO-incompatible liver transplantation in children are similar to those of ABO-compatible transplan- tation. We conclude that ABO-incompatible liver transplantation is reasonable in urgent cases for recipients of all age groups and for children without possible ABO-compatible living related donors.